1996
DOI: 10.1021/bi9603635
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Change in Human DNA Repair Enzyme O6-Methylguanine-DNA Methyltransferase upon Alkylation of Its Active Site by SN1 (Indirect-Acting) and SN2 (Direct-Acting) Alkylating Agents:  Breaking a “Salt-Link”?

Abstract: Human O6-methylguanine-DNA methyltransferase (MGMT) repairs DNA by transferring alkyl (R-) adducts from O6-alkylguanine (6RG) in DNA to its own cysteine residue at codon 145 (formation of R-MGMT). We show here that R-MGMT in cell extracts, which is sensitive to protease V8 cleavage at the glutamic acid residues at codons 30 (E30) and 172 (E172), can be specifically immunoprecipitated with an MGMT monoclonal antibody, Mab.3C7. This Mab recognizes an epitope of human MGMT including the lysine 107 (K107) which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…These results suggested that, upon the repair of 6MG, MGMT undergoes a conformation change in vivo as indicated by the masking of these previously exposed N and C termini. This agrees with the specific cleavage of R-MGMT by protease V8 in vitro at glutamic acid residues E30 and E172 flanking the N and C termini of MGMT (35).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results suggested that, upon the repair of 6MG, MGMT undergoes a conformation change in vivo as indicated by the masking of these previously exposed N and C termini. This agrees with the specific cleavage of R-MGMT by protease V8 in vitro at glutamic acid residues E30 and E172 flanking the N and C termini of MGMT (35).…”
Section: Discussionsupporting
confidence: 86%
“…To understand whether the rapid disappearance of MGMT speckles upon NMU treatment was due to DNA damage and repair by MGMT, we analyzed the amount of R-MGMT formed in these NMU-treated cells and the ability of MGMT.PAb to immunoprecipitate active MGMT and R-MGMT. The R-MGMT was quantified by the protease V8-Western blot method (35), by which R-MGMT appeared as two distinctive 14-and 18-kDa polypeptides after cleavage by protease V8. Figure 6c, subpanel A, shows that the levels of total cellular MGMT remain constant (therefore, no degradation) in all samples.…”
Section: Rapid Disappearance Of Mgmt Speckles Upon Treatment With Nmumentioning
confidence: 99%
“…GST-(wt) and MGMT (K107L) were prepared as described previously (26). Recombinant ER-␣ (50 ng; Oncogene Science) was added to buffer B (100 l of 50 mM HEPES [pH 7.3], 0.1% Triton X, 10% glycerol, 100 mM KCl, and 1 mM dithiothreitol) with glutathione-Sepharose (20 l of a 50% suspension)-bound fusion proteins (ϳ100 ng) which were first treated with bovine serum albumin (100 l of 20% bovine serum albumin in buffer B) at 4°C for 1 h. After shaking at 4°C for 15 min, the beads were recovered and washed three times with 500 l of buffer B before boiling in Laemmli buffer for immunoblot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate human R-MGMT function, we treated some MGMT-positive (mer ϩ ) and -deficient (mer Ϫ ) cells with 6BG, which alkylates selectively the cysteine C145 residue of human MGMT without causing DNA damage (26). Flow cytometry (FC) analysis of these 6BG-treated cells in Fig.…”
Section: Bg Inhibits the Growth Of Breast Cells Expressing Er And Mgmentioning
confidence: 99%
See 1 more Smart Citation